Non-Invasive Assessment of the Seasonal Stress Response to Veterinary Procedures and Transportation of Zoo-Housed Lesser Anteater (Tamandua tetradactyla) - Gabina V. Eguizábal; Mariella Superina; Rupert Palme; Camila J. Asencio; Daniel P. Villarreal; Luciana Borrelli; Juan M. Busso (Animals, 2021)
Management procedures affect behavioural and physiological stress responses of wild mammals under human care. According to the Reactive Scope Model, normal values are presumed to exist within predictive and reactive ranges. First, stress parameters of zoo-housed adult Tamandua tetradactyla were evaluated in winter and summer (29 days each), determining the level of behaviour and/or physiological parameters needed to respond to predictable environmental changes. Secondly, the effects of veterinary procedures and transportation were studied in both seasons. Non-invasive methods were applied, assessing behaviour through videos and adrenocortical activity by faecal glucocorticoid metabolites (FGMs). Lesser anteaters exhibited seasonality (summer > winter) in some behavioural parameters, such as nocturnal activities, as well as in the activity cycle (e.g., acrophase) and FGMs. A veterinary check elicited an increase in total activity (TA), natural behaviours and repetitive locomotion and affected the activity cycle, particularly in summer. Transport produced changes in TA, nocturnal and natural activity and some variables of the activity cycle, mostly during summer. Although the effects of routine management procedures were different from each other and presumably stressful, they elicited changes only at the behavioural level, which was greater during summer. The differences observed according to non-invasive methodologies highlight the importance of a multidisciplinary approach in this context and suggest that it is unlikely that individual welfare was affected.